Technical Economy Study on Jurang Jero Small Dam Construction Project In Blora Regency - Dedi Prasetio Suryono; Soedarsono Soedarsono; Gata Dian Asfari (International Conference on Coastal and Delta Areas, 2017)
One effort to improve the water resources sector in the field of water needs is to build a container of water reservoir either in the form of natural container shelters like situ or artificial storage containers such as small dam. The aim of this research is to know the benefits of Jurang Jero small dam construction in terms of technical economic aspects obtained from irrigation water and raw water for Jurang Jero small dam construction project. The research method is descriptive quantitative with NPV analysis technique, Net B / C, IRR and sensitivity analysis. Quantitative data in the form of project costs, agricultural and fishery data are needed to calculate project benefits. Primary data retrieval technique using interview. Keywords: ekonomi teknik, small dam, Jurang Jero